2002
DOI: 10.1007/s11661-002-0397-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure/processing relationships in reaction-synthesized titanium aluminide intermetallic matrix composites

Abstract: Near-␥ TiAl-and Al 3 Ti-based intermetallic matrix composites have been produced using in-situ reaction-synthesis techniques. The intermetallic matrices have been reinforced with relatively high loadings (e.g., 20 to 50 vol pct) of dispersed TiB 2 particulates. It is shown that the as-synthesized TiB 2 size is strongly dependent on the specific alloy formulation; specifically, the TiB 2 size tends to increase as the nominal volume percent of TiB 2 in the composite increases. The observed size effect is determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…If conditions are conducive to co-deformation, both components will commensurately deform, creating a multilithic metal matrix composite (MMMC) with approximately aligned DR-IMC "reinforcement" of an increased aspect ratio as a consequence of the deformation imposed. [10,11,12] …”
Section: A Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…If conditions are conducive to co-deformation, both components will commensurately deform, creating a multilithic metal matrix composite (MMMC) with approximately aligned DR-IMC "reinforcement" of an increased aspect ratio as a consequence of the deformation imposed. [10,11,12] …”
Section: A Generalmentioning
confidence: 99%
“…The DR-IMC component was comprised of variations of Al 3 Ti or the Ti-47Al matrix composites, discontinuously reinforced with a dispersion of TiB 2 particulate. Details of the process, synthesis, densification, and monolithic deformation behavior of these DR composites have been presented previously; [8,10,13] however, the process will be briefly summarized here. The DR-IMC composites were produced using an in-situ, reaction-synthesis technique.…”
Section: B Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sintering temperature is lower than the melting point of Al, Ti and Al diffuse to form TiAl 3 phase on the particle boundary. 8) At the Al melting point temperature, the diffusion velocity of Al in Ti is 0.075 mm/s and vise verse is 0.066 mm/s. In addition, Al element is main diffusion unit in the Ti-Al diffusion system because the solid solubility of Al in Ti is much more than that of Ti in Al.…”
Section: The Influence Of Pressing Pressure On Pore Charactermentioning
confidence: 95%
“…Previous studies have demonstrated the reaction synthesis of metal aluminides from elemental powders, including those based on titanium [1,2], nickel [3][4][5][6][7][8][9], iron [10][11][12][13][14], zirconium, niobium [15] and tantalum [3]. Concurrent and post synthesis hot pressing has often been used in combination with reaction synthesis to improve the density of the aluminides produced [3,6,7,13].…”
Section: Introductionmentioning
confidence: 99%